Pengenaan Pajak Pertambahan Nilai, Pajak Kendaraan Bermotor, dan Daya Beli Konsumen - Prabawati, Ida Ayu Adinda; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2023)
Consumer purchasing power is influenced by the imposition of Value Added Tax (VAT) and Motor Vehicle Tax (PKB). The aim of this research is to examine the effect of the imposition of VAT and PKB on consumers' purchasing power. This research was conducted at the Denpasar City Samsat office, the number of samples used was 100 taxpayers using the Slovin formula convenience sampling method. Data collection was carried out using a survey method, where the survey instrument was in the form of a questionnaire. The collected data was then analyzed using multiple linear regression analysis techniques. The research results show that the imposition of VAT has a positive effect on consumer purchasing power and the imposition of motor vehicle tax has a negative effect on consumer purchasing power. Keywords: Imposition of Value Added Tax; Vechile Tax; and Consumer Purchasing Power.